Differences in access and utilisation of mental health services in the perinatal period for women from ethnic minorities—a population-based study - Jelena Jankovic; Jake Parsons; Nikolina Jovanović; Giles Berrisford; Alex Copello; Qulsom Fazil; Stefan Priebe (BMC Medicine, 2020)
Abstract Background Barriers to accessing mental health care during pregnancy and the first postnatal year (perinatal period) seem to be greater for ethnic minority women; however, there is no reliable large-scale data about their actual use of mental health services during this period. Our study aims to explore access rates to secondary mental health services, including involuntary admissions to psychiatric inpatient care and patterns of engagement for ethnic minority women aged 18+ who gave birth in 2017 in England, UK. Methods Two datasets from the National Commissioning Data Repository, the Acute Inpatient Dataset and Mental Health Services Dataset, were linked. Datasets covering the full perinatal period for each woman were included. Rates were standardised by age and deprivation. Results Out of 615,092 women who gave birth in England in 2017, 22,073 (3.5%) started a contact with mental health services during the perinatal period. In total, 713 (3.2%) were admitted to inpatient care, and 282 (39.5%) involuntarily. Ethnicity data was available for 98% of the sample. Black African, Asian and White Other women had significantly lower access to community mental health services and higher percentages of involuntary admissions than White British women. Black African, Asian and White Other women had a higher number of attended community contacts and fewer non-attendances/cancellations of appointments than White British women. Conclusion Access to mental health services during the perinatal period varies significantly between women from different ethnic groups. Access to community mental health services should be facilitated for Black African, Asian and White Other women during the perinatal period, which may reduce rates of involuntary hospital admissions for these groups. The pattern of engagement with community services for women from these ethnicities indicates that access appears to be a problem rather than utilisation.